Utrecht, Britain and the Continent
1 online resource
Keywords: This book presents the latest research on the cities monuments from the arrival of Willibrord and Boniface and the establishment of the Bishopric. It focuses on 12th century sculptural iconography, manuscript production, fonts, secular architecture and the Gothic cathedral.